2000
DOI: 10.1021/jp993242y
|View full text |Cite
|
Sign up to set email alerts
|

Penning Ionization of (NH2)2CX (X = O, S) with He*(23S) Metastable Atoms. Difference of Anisotropic Interaction around N, O, and S Atoms

Abstract: The anisotropic interaction potential energy surface around urea and thiourea ((NH2)2CX, X = O,S) with the He*(23S) metastable atom has been studied by two-dimensional (collision-energy/electron-energy-resolved) Penning ionization electron spectroscopy and by model potential energy calculation for the molecule−Li system based on a well-known resemblance between a metastable excited He*(23S) atom and a ground-state Li(22S) atom. A different trend was found in the interaction around the CX (X = O, S) group; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Collision Energy Dependence of Partial Ionization Cross Sections (CEDPICS). Partial ionization cross sections obtained in the present study show mostly negative collision energy dependence, which is considered to be due to highly attractive interactions around nitrogen and oxygen atoms. 14c, Very large negative slopes of m = −0.60 and m = −0.51 were found for the n N bands in MMA and EA, respectively. Such a large negative slope for amines can be related to a deep attractive potential well around the N atom which is free from the hydrogen bonding of an OH···N type.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Collision Energy Dependence of Partial Ionization Cross Sections (CEDPICS). Partial ionization cross sections obtained in the present study show mostly negative collision energy dependence, which is considered to be due to highly attractive interactions around nitrogen and oxygen atoms. 14c, Very large negative slopes of m = −0.60 and m = −0.51 were found for the n N bands in MMA and EA, respectively. Such a large negative slope for amines can be related to a deep attractive potential well around the N atom which is free from the hydrogen bonding of an OH···N type.…”
Section: Discussionsupporting
confidence: 47%
“…An experimental technique 10 has been developed to obtain two-dimensional PIES (2D-PIES) in which ionization cross sections are as functions of both electron kinetic energy ( E e ) and collision energy ( E c ). Collision energy dependence of partial ionization cross sections (CEDPICS), which reflects anisotropic interactions between M and He*, has been observed for N 2 and some simple molecules, organic molecules including heteroatoms, benzene, , substituted benzenes, , and an organometallic compound …”
Section: Introductionmentioning
confidence: 99%
“…By studies of 2D-PIES for (NH 2 ) 2 C@X (X ¼ O, S) [14] and (NH 2 )CX(CH 3 ) [15], a large ring-like attractive well of interaction potential was found to be in perpendicular directions around the C@S axis, while collinear direction of the C@O axis was the most attractive one. A recent study for 2D-PIES of CS 2 [16] indicated attractive interaction for the perpendicular direction of the molecular axis and some satellite bands arising from configuration interactions or excitation transfer from He à to CS 2 .…”
Section: S) Ismentioning
confidence: 97%
“…71 meV for 119°of the He à -O-C angle. In the case of Li and (NH 2 ) 2 C@S [14] or (NH 2 )CS(CH 3 ) [15], deep potential wells more than 300 meV were calculated for 90-100°of the Li-S-C angle mainly due to large interorbital interaction between HOMO (S 3p , ca. )8 $ )9 eV by first IPs) and the 2s orbital of Li (ca.…”
Section: Trajectory Calculation and Potential Optimizationmentioning
confidence: 99%
“…Interaction potential energy surfaces between M and He*(2 3 S) in various directions and distances were modeled by approximating the M-He(2 3 S) surfaces with those of Li(2 2 S)-M based on the well-known resemblance between He*(2 3 S) and Li(2 2 S); similar shape for the velocity dependence of the total scattering cross section and for the location and depth of the attractive potential well for He*(2 3 S) and Li(2 2 S) with various atomic targets. Recently, a precise estimate of the similarity has been made for atomic targets; the well depths for the Li + Y (Y = H, Li, Na, K, Hg) systems were found to be 1.1∼1.2 times larger than those for He*(2 3 S) + Y. Although for molecular targets M, a direct comparison between the interactions of Li + M and He* (2 3 S) + M has never been reported so far, the observed peak energy shifts between PIES and UPS, which were relevant to the interaction potentials between the reagents, were well-reproduced by the Li + M potentials calculations for numerous compounds. Because of these findings and the difficulties associated with calculation for excited states, the Li was used in this study in place of He*(2 3 S). Thus, the interaction potential M-Li(2 2 S), V *( R ) (where R is the distance between Li atom and either F atom or the center of the benzene ring), was calculated by moving the Li atom toward either F atom or the center of the benzene ring and keeping the molecular geometries fixed at the experimental values; this assumption meant that the geometry change during the approach of a metastable atom was negligible in the collisional ionization process.…”
Section: Calculationsmentioning
confidence: 99%